2011
DOI: 10.1007/s12524-011-0092-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Studies Using Space Based Observation

Abstract: Climate change is associated with earth radiation budget that depends upon incoming solar radiation, surface albedo and radiative forcing by greenhouse gases. Human activities are contributing to climate change by causing changes in Earth's atmosphere (greenhouse gases, aerosols) and biosphere (deforestation, urbanization, irrigation). Long term and precise measurements from calibrated global observation constellation is a vital component in climate system modelling. Space based records of biosphere, cryosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…With this input into the simulation models, prediction of the impact of climate change can be made, which in turn can help in planning adaptation measures † . 11 gives several examples of the use of space-based facilities and observations on climate change studies in the Indian context.…”
Section: Institutions Of the Department Of Spacementioning
confidence: 99%
“…With this input into the simulation models, prediction of the impact of climate change can be made, which in turn can help in planning adaptation measures † . 11 gives several examples of the use of space-based facilities and observations on climate change studies in the Indian context.…”
Section: Institutions Of the Department Of Spacementioning
confidence: 99%
“…Another significant study carried out by Srisudha et al (2013) showed that C-band FRS-1 image mode data from RISAT-1 mission can be effectively employed for the identification and monitoring of ice floes in the polar regions. According to Navalgund et Singh (2011), Resourcesat-1 can be used for effective mapping/detecting the indicators of climate change, study glacier retreat, and changes in polar ice cover.…”
Section: Introductionmentioning
confidence: 99%
“…Groundbased observations of these variables are not homogenous across the country and consequently they are not sufficient enough to monitor various aspects of drought. A constellation of the Earth-observation satellites provides reasonable precipitation, soil moisture, temperature, and vegetation estimates at regular spatio-temporal intervals 11,12 . However, these datasets are available for a rather short period of time, e.g.…”
mentioning
confidence: 99%